A “Guerra dos 18 anos” : repertórios para existir e resistir à ditadura e a outros fins de mundo : uma perspectiva do povo indígena Xakriabá e suas cosmopolíticas de memória - Juliana Ventura de Souza Fernandes (2020)
This PhD dissertation is a study of military dictatorship (1964-1988) from the point of view of the Xakriabá, whose indigenous territory is located in the North-east of the state of Minas Gerais. In terms of methodology, this research study draws from concepts of ethnohistory, ethnography, testimonial historiography, and contributions derived from the interplay of historiography, anthropology, and indigenous epistemologies. Theoretical approaches seeking to interpret the experience of contact between indigenous peoples and the non-indigenous world by means of the “hybridity as mestizaje” discourse have been avoided, whereas those looking at the possibility of indigenous agency that would not rely on what is generally understood as “syncretism” have been considered. Therefore, theories that analyze processes that could be understood as counter- or anti-miscegenation were preferred, thus highlighting traditional concepts of the Xakriabá and the ways indigenous people think and make sense of their own experiences. In this way, the military dictatorship, from the perspective of the Xakriabá - conceived as a “war” - and their own understanding of temporality (“the time of the struggle for land” or “The Eighteen Years’ War”), can not be grasped simply by the perspective of “resistance.” Although the struggles against intrusions of the State are of special relevance in the experiences lived, the ways the Xakriabá understand and experience the temporality of the military dictatorship point to specific strategies of existence or practices of “world-making,” sustained by their own cosmovision. Generally on the margins of academic writing on the historiography of military dictatorship, such strategies and practices help to shape a native historiographic process, based on counter-miscegenation and counter-colonialism. This work also focuses on the understanding of how contemporary Xakriabás relate with such past events and what they make of that past now. When dealing with that past, complex processes of “cultural reclaiming” and “memory reactivation” can be observed, although they don’t solely indicate a perspective of return to the past or tradition. In spite of the fact that the teachings of their “ancestors” are key elements of their agency, such practices unveil projects and possibilities of indigenous becoming, entailing ways of “peoplemaking” and healing the Xakriabá territory, which includes humans, non-humans, the Cerrado, “the ancestors,” contemporary Xakriabá and “the ones still to come.”